Pengukuran Kinerja Departemen Fresh Food Tiara Dewata Supermarket Denpasar dengan Metode Balanced Scorecard - Lianingsih, Tejawati; Satriawan, I Ketut; Yoga, I.W.G. Sedana (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2019)
This research was conducted at the Department of Fresh Food Tiara Dewata Supermarket, Denpasar. The purpose of this study was to measure the performance of the Fresh Food Department at Tiara Dewata Supermarket with the Balanced Scorecard method and determine the actions that companies need to take to improve performance. This research was conducted by observation to the location, interviews with management and the distribution of questionnaires to respondents. The results showed that the total performance score on each perspective was a financial of 38.53%; a customer perspective of 33.05%; an internal business process perspective of 9.44%; and a learning and growth perspective of 23.10%. Based on the criteria of the total score of performance appraisal shows that Tiara Dewata Supermarket is in a "Very Healthy category (AAA)" condition with a total overall performance score of 104.12%. The action that needs to be taken by Tiara Dewata Supermarket is to maintain performance on the perspective that the value has reached the target, namely sales growth and employee training level. Companies also need to improve and improve performance on the level of customer satisfaction, the level of customer perception of fresh food products, lead time processes, defective products, employee retention rates, attendance levels and employee satisfaction levels at a perspective that has not yet reached company targets. Keywords : performance measurement, balanced scorecard, tiara dewata supermarket